Pengaruh Live Streaming dan Diskon terhadap Perilaku Impulsif Konsumen Muslim pada Pengguna Tiktok Shop di Kabupaten Bone - Risda Alimuddin; Ahmad Abdul Mutalib; Muh. Hasbi Ash. Shiddiq (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study analyzes the effect of live streaming and discounts on impulsive behavior of Muslim consumers on TikTok Shop users in Bone Regency. The purpose of this study was to test whether live streaming and discounts affect impulsive behavior of Muslim consumers on TikTok Shop users in Bone Regency. The study used a quantitative method with data collection techniques through questionnaires. The results showed that there was a significant influence between live streaming on impulsive behavior of Muslim consumers on TikTok Shop users in Bone Regency. This is indicated by a p-value of 0.009 <0.05 or a t-statistic of 6.900> 1.661. There is a significant influence between discounts on impulsive behavior of Muslim consumers on TikTok Shop users in Bone Regency. This is indicated by a p-value of 0.000 <0.05 or a t-statistic of 2.616> 1.661. The Big Influence of Live Streaming and Discounts on Impulsive Behavior of Muslim Consumers on TikTok Shop Users in Bone Regency with an R Square value of 0.915, this means that 91.5% of the variation or change in impulsive behavior of Muslim consumers is influenced by live streaming and discounts, while the remaining 8.5% is explained by other causes.